Efek Paparan Rhodamin B Terhadap Perubahan Makroskopis Dan Histopatologi Mukosa Kolon Mencit Jantan (Mus musculus L.) - Novita Aryani (Pascasarjana Universitas Negeri Medan, 2015)
Abstract. Rhodamine B is a synthetic dye that can not be used as food additives and harmful if it enters the body, causing oxidative stress if continued resulting in cell membrane damage and cell death, but until now its use is still found in industrial-scale food production and household . The aim of research to determine the effect of rhodamine B exposure and after cessation of exposure rhodamine B (recovery period) to the macroscopic and histopathological changes in the colonic mucosa of mice (Mus musculus L.) males. This study tested an experimental laboratory to design the post-test only control group. The research subject of male mice (Mus musculus L.) strains DD Webster, 6-7 weeks, 25-40 grams, 28 were divided 2 treatment groups: (1) P0 (control) were given distilled water 0,3ml, (2) rhodamine B dose 0.2% / day, 0,3ml. Treatment for 21 days, then continued for 7 days without any treatment to see his cell recovery. The results showed a significant increase (p <0.5) macroscopic colonic damage and histopathology colonic mucosa in the treatment group compared with the control group when treated well after treatment is stopped. Expected to society, especially with children under five and school age do not consume snacks bright. Keywords: rhodamine B, macroscopic, histopathology, colon mucosa